Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.18502/jabs.v13i2.12729
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of HPV Genotypes 16 and 18 Found in Breast Cancer Patients: Evidence for a More Comprehensive HPV Vaccination Program in Iran

Abstract: Background & Objectives: Papillomaviruses are found in many different types of infections and in a wide range of animals and humans. They can cause health problems, including benign and malignant tumors. In the present study, the association between human papillomavirus (HPV) infection and breast cancer (BC) in Iran was investigated. Materials & Methods: In this cross-sectional study, the presence of the HPV genome was investigated in BC-suspected tissues for the first time in Qom Province, Iran.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Madadgar Omid and et al showed that Out of 200 breast cancer suspected tissue samples Based on the nested PCR method, the L1 gene of HPV was detected in 12% (24/200) of the BC-suspected tissue samples The high-risk HPV genotypes (which were the predominant types) were present in 75% of the samples. [51] Such these ndings suggest that HPV may play a role in the development of breast cancer in this population. The study has several implications for breast cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Madadgar Omid and et al showed that Out of 200 breast cancer suspected tissue samples Based on the nested PCR method, the L1 gene of HPV was detected in 12% (24/200) of the BC-suspected tissue samples The high-risk HPV genotypes (which were the predominant types) were present in 75% of the samples. [51] Such these ndings suggest that HPV may play a role in the development of breast cancer in this population. The study has several implications for breast cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 90%
“…Researchers have detected various HPV types worldwide, including in Iran, concerning studies investigating the role of HPV in breast cancer [8]. These types include 6, 11,15,16,18,23,33,35,45,51,52, 58, and 124, which have been identi ed in laboratory samples of breast cancer and HPV [9]. Although breast cancer is not a transmissible or infectious disease, given the con icting studies globally and the high prevalence of breast cancer among women, The study aimed to examine the frequency of HPV types in breast cancer samples among women in Ardabil province, Iran, to determine the role of HPV in breast cancer in this population.…”
Section: Introductionmentioning
confidence: 99%